Indigenous Practices of Maternal and Child Health Care Among the ManoboMatigsalug Tribe in Sitio Simsimon, Barangay Kalagangan, Valencia , Bukidnon - Ramos, Arnulfo B. (JPAIR Multidisciplinary Research, 2008)
The study documented the native knowledge, beliefs, and practices on maternal and child health care among the Manobo-Matigsalug Tribe in Sitio Sil-simon, Barangay Kalagangan, Valencia, Bukidnon. It focused on areas such as pregnancy, dietary systems, birthing, feeding, baptismal rituals, illnesses, and discipline. Despite previous studies on the tribe, none had thoroughly explored these specific issues. Employing an ethnographic design with descriptive and narrative presentation, data were gathered through fieldwork using key informant interviews, in-depth interviews, participant observation, and photography. Participants included traditional healers, tribal leaders, mothers, and children over seven months of research. Findings revealed that pregnant women observed taboos to protect their infants’ lives and health. The Babaylan served as both birth attendant and consultant. Mothers ensured their children’s health by avoiding stress and engaging in proper dietary practices. Birth was a significant event celebrated by the community, where relatives welcomed the newborn with care and affection. However, Manobo-Matigsalug mothers require improved knowledge of hygiene and nutrition to enhance maternal and child healthcare. Recommendations include local government support for developing herbal plant uses and providing the tribe with information from this study to guide improvements in traditional practices. Collaboration with schools offering courses in education, early childhood development, special education, and psychology is suggested for training programs. An orientation on child life programs should also be integrated into hospital workforce training. Further studies on other tribal groups in Mindanao are encouraged to expand understanding of indigenous healthcare practices.